Attention on adolescent mental disorders: the long-term effects on labor market outcomes - Yu, Jia (International Journal of Applied Economics, 2019)
According to a presidential task force about national college health in 2005, 14.9% of college students have been diagnosed with depression or anxiety disorders. Almost 75% of them experienced mental health problems during their early childhood or adolescence. Specifically, this paper examines the longitudinal effects of learning disability and attention disorder, and behavior disorder, of children born in 1980 – 1984, on their labor market outcomes as young adults. This study applies data from the National Longitudinal Survey of Youth 1997 (NLSY97), which documents the transition from school to work, and from adolescence to adulthood. By applying a family fixed effects model with Heckman selection procedure and multinomial logistic regression, the research results show that experiencing mental health illness during childhood is associated with a decreased risk of employment, an increased risk of unemployment, and decreased weekly paid working hours. This effect is strong and significant for males, and barely discernible for females. Hence, childhood mental disorder is an important determinant of individual’s labor market outcomes. Targeting the improvement for boys’ mental illness situation might be beneficial for improving their labor market participation.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Challenges and Futures of Long-Term Care Industry after COVID-19 Pandemic - Yu, Jia (Psychosocial, Educational, and Economic Impacts of COVID-19, 2022)
COVID-19 pandemic has affected people’s daily life dramatically since December 2019. More than 211 million cases and 4.42 million deaths have been reported and confirmed all over the world. Long-term care facilities are taking the biggest hit during this pandemic, even after the spread-out of the vaccines. Globally, residents in long-term care facilities have experienced disproportionately high morbidity and mortality from COVID-19. Elderlies residing in long-term care facilities have the greatest susceptibility to COVID-19 and the poorest outcomes from infections. This chapter overviewed the insight, impact, and challenges of COVID-19 on the residential care homes in UK, US, and Australia and provided possible implications for the long-term care market post-pandemic.
Keywords: dept.eco

Parental Education Matters for Adolescent Health: The Importance of Parental Education in the US - Yu, Jia (Journal of Studies in Social Sciences, 2015)
Parental Education Matters for Adolescent Health: The Importance of Parental Education in the US
Keywords: dept.eco

Will social participation make retirees happier? An empirical study about retirement life in China - Zhao, Luman; Yu, Jia (Journal of Applied Business and Economics, 2025)
How elderlies participate in social activities is a key issue in coping with aging and has an important impact on elderlies’ well-being. This paper examines the effects of different social participation patterns on the happiness of the elderlies in China. The empirical analysis was conducted based on the data from the China Household Finance Survey (CHFS) in 2015. The research results show that compared with reemployment after retirement, community governance is a more common way for retired people to be involved in social activities. We found that reemployment significantly reduces the happiness degree of the retired. Furthermore, this negative effect is more significant in samples without a formal labor contract, relatively lower education level, & senior retired people. In contrast, participating in community governance can significantly improve the happiness level of retirees, which is more essential in the sample of the medium education level and junior retirees.
Keywords: Business; China; Demographic economics; Economics; Empirical research; Labour economics; Life satisfaction; Political science; Psychology; Social psychology; dept.eco

Comparison of Single-Payer and Non Single-Payer Health Care Systems: A Study of Health Administration Efficiency - Yu, Jia; Zhang, Yi (Modern Economy, 2017)
The United States spends nearly twice as much per capita on health care as several OECD countries. Based on previous research, universal health care decreases the total health care expenditure due to the single-payer system; it is still unknown whether a mixed health care system has superiority. In this study, we compare and evaluate both quality of care and administrative costs among six developed countries, upon three groups: single-payer universal health care system (Australia and Canada), two-tier health care system (France and Japan), and insurance mandate health care system (Switzerland and the US). The results show that both single-payer system and two-tier system are superior to insurance mandate system on health insurance administration costs. Also, regarding insurance mandate system, the healthcare system in Switzerland is more efficient than that in the US. So, we conclude that it is possible for the US to choose a diverse healthcare system, instead of focusing on one system, to trim the healthcare administration cost and improve the quality of care for the entire country.
Keywords: dept.eco

‘Is it wise to open up America again now?’ Learning from government responses to COVID-19 and economy reopen points in three Asia-Pacific countries - Yu, Jia; Pang, Yulei (British Journal of Healthcare Management, 2020)
With the continuously increasing number of new confirmed COVID-19 cases, many health experts worried about the possibility of a ‘second wave’ outbreak, which might cause more deaths and hit economies even worse. This article looks at the experiences of fighting COVID-19 from three Asia-Pacific countries and discusses whether it is a wise decision to open up America again at this time.
Keywords: dept.eco; dept.mat; peer-reviewed

International comparison on economics impact from the COVID-19 pandemic: policy analysis - Supple, Brandon; Yu, Jia (Medical Research Archives, 2023)
Keywords: SCSU-student; dept.eco; peer-reviewed

No more nursing homes? Changes in consumer preferences for long-term care facilities following COVID-19 - Schultz, Amber F; Yu, Jia (British Journal of Healthcare Management, 2020)
Since the first COVID-19 case was discovered in December 2019, over 12.1 million cases have been reported in more than 188 countries and territories. In the USA, the Centers for Disease Control and Prevention has confirmed almost 3.05 million COVID-19 cases, with more than 132 000 deaths. The COVID-19 pandemic has had a particularly dramatic impact on the elderly and those with chronic underlying medical disorders. Before the second outbreak in July, long-term care facilities were the most severely affected in terms of case numbers, especially nursing homes. This article provides information and insight into the potential changes in consumer preferences toward long-term care facility selection and the possible structural change of the long-term care industry in three aspects; structure, conduct and performance. © 2020 MA Healthcare Ltd. All rights reserved.
Keywords: Covid-19; Home care service; Long-term care facility; Nursing home; dept.eco; peer-reviewed

Unlocking Opportunities for Migrant Workers in China: Analyzing the Impact of Health Insurance on Hukou Switching Intentions - Chen, Hong; Yu, Jia; Qin, Mingshuai; Wang, Yangyang; Qin, Lijian (Sustainability, 2023)
The Chinese urban–rural binary health insurance structure has contributed to a significant urban–rural segmentation and regional fragmentation, which will affect labor mobilization and urbanization. The purpose of this research is to study whether and how urban–rural binary health insurance impacts the intentions of migrant workers to switch between rural and urban hukou. Pooled data were drawn from China Migrants Dynamic Survey, collected by the National Health Commission of China. The study applied the instrument variable model due to the existence of the endogeneity; and the IVprobit model to conduct the empirical analysis. Our findings are as follows: (1) the urban–rural binary health insurance affects migrant workers’ intentions to switch to urban hukou significantly. (2) The negative impact of originally rural health insurance on migrant workers’ intention of switching to urban hukou is relatively large for low-education-level migrant workers. (3) Compared with new generation of migrant workers, old migrant workers have higher health insurance dependency levels. Finally, our research suggested several policy implications, such as accelerating the establishment of a unified urban–rural health insurance system, increasing the urban health insurance participation rate of migrant workers in their working cities, and including migrant workers in the scope of equal access to urban public services, etc. All the policy suggestions are essential in order to accelerate the citizenization of migrant workers, improve the quality of urbanization, and promote the construction of a unified national labor market.
Keywords: dept.eco; intention of switching to urban hukou; migrant workers; peer-reviewed; urban–rural binary health insurance

Joining farmers’ cooperatives leads to equitable poverty reduction in China – empirical evidence from the rural households survey - Zhang, Ze; Qin, Lijian; Jia, Yu; Li, Yuheng; Hong, Chen; Qin, Wenshuai (Applied Economics, 2025)
Keywords: China; Empirical evidence; Inequality; Poverty; Poverty reduction; Rural poverty; Survey data collection; dept.eco

How human capital prevents intergenerational poverty transmission in rural China: Evidence based on the Chinese general social survey - Chen, Hong; Yu, Jia; Zhang, Ze; Li, Yuheng; Qin, Lijian; Qin, Mingshuai (Journal of Rural Studies, 2024)
Keywords: dept.eco; peer-reviewed